Pengaruh Permainan Tradisional Terhadap Kebugaran Jasmani Siswa Sekolah Dasar : Systematic Literature Review - Putri, Wanda Kusuma; Anggita, Gustiana Mega; Ali, Mohammad Arif; Sugiarto, Sugiarto; Ahda, Zahrah Zakiya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effect of traditional games on the physical fitness of elementary school students. The method used is descriptive qualitative with a systematic literature review model. The sources used came from Google Scholar, Research Gate and journals or articles relevant to the research title from publication years 2014 to 2023. The keywords used in searching for sources were traditional games, physical fitness, and elementary school students. 7 references were found to be used as main data. From the data obtained, this research found that traditional games have a positive influence in improving the physical fitness of elementary school students. Conclusion, traditional games can improve the physical fitness of elementary school students Keywords: elementary school students, physical fitness, traditional games